Analysis of Metacognitive Ability of Middle School Students in Science Learning by Using Reflection Blogs - Astutik, Kartika Fitri; Wusqo, Indah Urwatin (Journal of Environmental and Science Education, 2023)
This study aims to analyze the metacognitive abilities of junior high school students through reflection blogs. This study uses the type of research One-Shot Case Study. The sampling technique in this study used a purposive sampling technique. Based on the questionnaire data, metacognitive ability was obtained with an average score of 155.5 or 78.94% in class VIII A and metacognitive ability with an average score of 153.15 or 55%. Similar to the results of the questionnaire, the data for writing reflection blogs on students showed a score of 66% in class VIII A and 63% in class VIII B. Based on these data, it was found that the metacognitive abilities of class VIII A and class VIII B students were in the high category.